Extragenital Testing for Neisseria gonorrhoeae and Chlamydia trachomatis in a Large HIV Clinic in the US South: Implementation and Epidemiology. Issue 2 (February 2021) - Pottorff, Alexandra; Duarte, Piper; Chow, Jeremy; Luque, Amneris; Nijhawan, Ank E.
Abstract : Background: Rectal and oral Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) infections are common among people with HIV, especially men who have sex with men (MSM); however, GC/CT testing rates remain low in many HIV clinics. We evaluated the real-world implementation and results of extragenital nucleic acid amplification testing for GC/CT in an urban HIV clinic. Methods: Electronic health records were reviewed for all patients 18 years or older with ≥1 outpatient visit to an HIV clinic in Dallas, TX, from February 2016 to May 2019. Extragenital nucleic acid amplification testing became available in February 2017, which was followed by active interventions to increase testing. Results: Overall, 5564 individual patients were included in the preintervention period (February 2016–January 2017), 5067 in the intervention period (February 2017–August 2017), and 7030 in the postintervention period (September 2017–May 2018). Tailored education was provided to patients, and nursing and medical providers, and a self-collection protocol was implemented beginning in spring 2017. A sustained increase in extragenital GC/CT testing among MSM patients, from 70% to 87% ( P < 0.01), was observed. Among MSM, overall GC positivity increased from 3.2% to 8.5% and CT positivity increased from 3.9% to 8.3%. N. gonorrhoeae / C. trachomatis infections were highest among young (<35 years) MSM, and approximately 50% of GC/CT infections diagnosed were detected by oral and rectal tests. Conclusions: Clinic-wide education and self-collection of extragenital specimens were associated with increased GC/CT testing and detection in a large HIV clinic. Abstract : A real-world quality improvement study was conducted to inform and evaluate the implementation and epidemiology of extragenital testing for sexually transmitted infections among patients in a large urban HIV clinic in the South.